2016
DOI: 10.1007/s11914-016-0326-z
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Targets for the Management of Osteoarthritis Pain

Abstract: Worldwide, osteoarthritis (OA) is one of the leading causes of chronic pain, for which adequate relief is not available. Ongoing peripheral input from the affected joint is a major factor in OA-associated pain. Therefore, this review focuses predominantly on peripheral targets emerging in the preclinical and clinical arena. Nerve growth factor is the most advanced of these targets, and its blockade has shown tremendous promise in clinical trials in knee OA. A number of different types of ion channels, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…In a recent study that used CRISPR/Cas9 technology to ablate OA-associated genes, although ablation of matrix metalloproteinase 13 (MMP-13) or interleukin 1beta (IL-1β) markedly attenuated structural deterioration, the extent of pain relief was modest compared to the ablation of NGF, which significantly increased joint damage, despite its profound analgesic effect [92]. In MNX-and MIA-induced OA of rats, it was shown that pain responses to NGF locally administered into the knee cavity were increased in OA compared to non-OA joints, indicating that local production of NGF may be crucial for the generation of pain [62,93]. In a DMM model, the loss of protein kinase C delta (PKCδ) expression prevented cartilage degeneration but exacerbated OA-associated hyperalgesia [94].…”
Section: Mnx (2 Wk)mentioning
confidence: 99%
“…In a recent study that used CRISPR/Cas9 technology to ablate OA-associated genes, although ablation of matrix metalloproteinase 13 (MMP-13) or interleukin 1beta (IL-1β) markedly attenuated structural deterioration, the extent of pain relief was modest compared to the ablation of NGF, which significantly increased joint damage, despite its profound analgesic effect [92]. In MNX-and MIA-induced OA of rats, it was shown that pain responses to NGF locally administered into the knee cavity were increased in OA compared to non-OA joints, indicating that local production of NGF may be crucial for the generation of pain [62,93]. In a DMM model, the loss of protein kinase C delta (PKCδ) expression prevented cartilage degeneration but exacerbated OA-associated hyperalgesia [94].…”
Section: Mnx (2 Wk)mentioning
confidence: 99%
“…Osteoarthritis (OA) is a chronic and progressive debilitating disease that affects 10e15% of the world's adult population and a leading cause of pain, disability, and reduction in quality of life 1,2 . Pain is the most prominent symptom of OA and can be caused by innocuous stimuli (termed mechanical allodynia) such as joint movement during walking 1 .…”
Section: Introductionmentioning
confidence: 99%
“…As understanding of the pathophysiology of OA pain has progressed, it has become apparent that much of the refractory pain associated with OA may be of neurogenic origin or may be responsive to neutralizing specific neurotransmitters (5, 6). Of the potential novel strategies for pain control in OA (7), clinical development is most advanced for strategies that target the neurotrophin, nerve growth factor (NGF). This narrative review provides a brief summary of the current status of NGF-blockade for the treatment of OA pain.…”
mentioning
confidence: 99%